2012
DOI: 10.1007/s11892-012-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Technology: Impact on Children and Families With Diabetes

Abstract: Ensuring quality of life (QOL) while maintaining glycemic control within targets is an important challenge in type 1 and type 2 diabetes treatment. For children with diabetes, QOL includes enjoying meals, feeling safe in school, and perceiving positive, supportive relationships with parents, siblings, and friends. Yet many treatment-related and psychosocial barriers can interfere with a child’s QOL and their ability to manage diabetes effectively. Diabetes management also imposes considerable lifestyle demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 111 publications
1
59
1
11
Order By: Relevance
“…Обучение -одно из показа-ний к непродолжительному использованию CGM-RT, когда целью данного способа самоконтроля становится не сиюминутное улучшение показателей гликемии, а создание у пациента правдоподобного представле-ния об истинных изменениях концентрации глюкозы в крови под влиянием различных факторов [20]. Это от-носится как ко взрослым пациентам, так и к детям, когда основная задача состоит в обучение семьи [32].…”
Section: углеводный обменunclassified
“…Обучение -одно из показа-ний к непродолжительному использованию CGM-RT, когда целью данного способа самоконтроля становится не сиюминутное улучшение показателей гликемии, а создание у пациента правдоподобного представле-ния об истинных изменениях концентрации глюкозы в крови под влиянием различных факторов [20]. Это от-носится как ко взрослым пациентам, так и к детям, когда основная задача состоит в обучение семьи [32].…”
Section: углеводный обменunclassified
“…Research has indicated a variety of psychosocial benefits and barriers to the use of these medical devices (Alsaleh, Smith, & Taylor, 2012;Hirose, Beverly, & Weinger, 2012;McCarthy, Rodríguez Ramírez, & Robinson, 2016;Ritholz et al, 2007). In one study, blood glucose testing was a source of social discomfort, with adolescents' self-management being influenced by observers, different contexts, and anticipated negative reactions to high or low blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Kasesniemi, 2003;Oksman and Rautiainen, 2003;Ito, 2005;Chen and Katz, 2009;Kaare et al, 2007;Plowman et al, 2010;Green et al, 2011Green et al, , 2012Green et al, , 2013Hertlein, 2012;Jackson et al, 2012;Palmer et al, 2012;Plowman and McPake, 2013;McPake et al, 2013;Livingstone et al, 2014b;Livingstone et al, 2015). Other studies address specific groups within these ages, such as children with diabetes (Hirose et al, 2012;Toscos et al, 2012), asthma (Mosnaim et al, 2012) intellectual and developmental disabilities (Palmer et al, 2012;Hwang et al 2014), complex communication needs (Light and McNaughton, 2012) and obesity (Woolford et al, 2012;Sharifi et al, 2013). In Europe, the most comprehensive studies have been produced by the EU projects, "EU Kids Online" 2 and "Net Children Go Mobile", 3 which conducted a panEuropean survey of interviews over 33,000 children (as well as some of their parents and teachers) between 2010-2014.…”
Section: Introductionmentioning
confidence: 99%